1985
DOI: 10.1084/jem.162.5.1726
|View full text |Cite
|
Sign up to set email alerts
|

Serological, biochemical, and functional identity of B cell-stimulatory factor 1 and B cell differentiation factor for IgG1.

Abstract: By three criteria, we have demonstrated that B cell stimulatory factor (BSF-1) and B cell differentiation factor (BCDF-gamma) are the same lymphokine. Highly purified preparations of high performance liquid chromatography-purified or affinity-purified BSF-1 had BCDF-gamma activity but not BCDF-mu activity. A monoclonal anti-BSF-1 antibody coupled to Sepharose depleted both BSF-1 and BCDF-gamma activity but not BCDF-mu activity from two different T cell supernatants. Soluble monoclonal anti-BSF-1 blocked the BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
1
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(155 citation statements)
references
References 17 publications
4
149
1
1
Order By: Relevance
“…This result is in agreement with previous findings that IL-4 inhibits the secretion of IgG2b and IgG3 and the production of c2b and c3 germline transcripts [16][17][18][19][20][21][22][23][24][25]. IL-4 was also found to inhibit the division-linked rate of switching to IgA.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in agreement with previous findings that IL-4 inhibits the secretion of IgG2b and IgG3 and the production of c2b and c3 germline transcripts [16][17][18][19][20][21][22][23][24][25]. IL-4 was also found to inhibit the division-linked rate of switching to IgA.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequent to biochemical purification (27) and molecular cloning (28,29), it was reported that II.,-4 and IgG1 enhancing factor, also called B cell differentiation factor-,/ (BCDF-~,), arc the same lymphokine (30). IL-4 was later shown to act also on T cells as well as on other cell types including monocytes, endothelial cells, and fibroblasts (13,31).…”
Section: Vol 40 No 6 1996mentioning
confidence: 99%
“…IL-4 has biological effects on many immune cells, including B and T lymphocytes, mast cells, and macrophages, and plays a central role in regulating inflammatory and cell-mediated immune responses (Nelms et al, 1999). IL-4 acts not only as a major determinant for Th2 cell differentiation, but it also controls the specificity of immunoglobulin B cells switching to the expression of IgE and IgG (Vitetta et al, 1985;Coffman et al, 1986;Gascan et al, 1991). In addition to the effect of immune cells, IL-4 has a variety of other functions including effects in hematopoietic tissues, tissue adhesion, and inflammation (Nelms et al, 1999).…”
Section: Introductionmentioning
confidence: 99%